Transformasi Pendidikan Islam Inklusif di Era Rasulullah ke Era Modern - Ari Wibowo; Rendi Rendi; Sherly Raihani; Ramedlon Ramedlon (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
The transformation of inclusive Islamic education from the era of the Prophet to the modern era shows a significant evolution in the approach to inclusive education. Where this research is focused on inclusive values taught by the Prophet so that it can be applied in the context of education today. Exploring and analyzing the paradigm change of Islamic education from exclusive to inclusive, as well as its urgency in facing modern challenges which is the goal of this article. By using a research literature study with a descriptive qualitative approach, which relies on reflective logical analysis of existing literature. Where this study shows that Islamic education in the era of the Prophet, which was marked by the Medina Charter, provides a real example of tolerance and respect for religious and cultural differences. Therefore, researchers are interested in studying it, because it emphasizes the need for improvements in curriculum elements, learning strategies, and educator training to create an educational environment that is inclusive and relevant to the needs of today's young generation. As a hope for the future to be able to foster an open and tolerant attitude among students.